The lady vanishes [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Lockwood, Margaret; Redgrave, Michael; Lukas, Paul, 1894-1971; Whitty, May, Dame, 1865-1948; Parker, Cecil, 1897-1971; White, Ethel Lina (Laserlight DVD, 1999)
On a train, an old woman mysteriously disappears. Two young people search for her and uncover a dangerous spy ring.